Arabic Language and Social Identity of Native Speaker Lecturers in Language Learning in Indonesia: A Narrative Study - Syafni, Hafidhah; Mustofa, Syaiful; Rusuly, Usfiyatur; Ridha, Muhammad (Al Mi'yar: Jurnal Ilmiah Pembelajaran Bahasa Arab dan Kebahasaaraban, 2025)
Arabic language learning in Indonesia has a crucial role, with various steps that can improve the effectiveness of its teaching. This article aims to find out the role of native Arabic speakers in the language learning process, the language and cultural gaps that occur, and learning reflections for the future. In this study, the researcher uses a narrative study method that makes a person's life experience the main data. The research data collection technique uses a story framework and interviews. To analyse the data, the researcher used the following steps: 1) The researcher collects data through story frameworks and interviews, 2) selects and classifies the information to facilitate its presentation, and 3) presents the data by processing the classified information based on temporal aspects and drawing conclusions. The results showed that 1) Arabic plays an important role in Indonesian education, which can be improved by involving native speakers in teaching. 2) The language and cultural gap between Indonesia and other countries can be overcome by simplifying the language and adjusting teaching methods and learning environments. 3) Reflection on curriculum development, facilities, and technological utilisation can support Arabic language acquisition, followed by high motivation to improve students' skills.